London : Mobility city (Volume 4) - Moonen, Tim; Clark, Greg; Nunley, Jack; European Investment Bank; European Investment Bank (European Investment Bank, 2018)
Despite the uncertainties of Brexit, London continues to be rated as a leading location in Europe and the world for business, knowledge, and talent. But 30 years ago, when London had no citywide government, a transport system in crisis, and no successful track record of continuous large-scale upgrades to the urban fabric, this scenario would have seemed highly unlikely. In this essay we examine how London's unpromising 1980s gave rise to three decades of reinvestment and we explain how the European Investment Bank played an essential catalytic role in successive cycles of London's evolution from an under-governed de-populating national capital into a diverse global centre benefiting from integrated urban systems management.
Knowledge Unlatched
English
Keywords: Finance; Business & Economics; Finance